DESCRIPTION OF DENTAL HEALTH ON ELDERLY PLENARY POSYANDU AT REGION OF PUSKESMAS III DENPASAR IN 2015 Diah - Diah Laksmi Atmaning Natha; Sagung Agung Putri Dwiastuti (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Generally, elderly has more experience physical setback, one of them is marked with loss teeth. The susceptible problem of dental and oral health which happened on elderly are dental caries and periodontal disease. In Indonesia, both diseases are the main cause elderly’s loss teeth. The purpose of this study was to describe the dental health on elderly plenary Posyandu at region of Puskesmas III North Denpasar in 2015. Research methods used in this research is descriptive method, and used 70 samples by proportional random sampling technic. Based on data analysis and discussion of the research results, from 70 elderly respondents only 27 respondents (38,57%) has ≥ 20 teeth function, while 43 respondents (61,43%) has   20 teeth function. As many as 41 respondents (58,57%) has anterior teeth function. The frequency of elderly who has posterior teeth function as many as 41 respondents (58,57%). The conclusion is mostly elderly on elderly plenary Posyandu at region Puskesmas III North Denpasar has less than 20 teeth function. There’s still a small portion of elderly who has not anterior teeth function and posterior teeth function.